Modeling the impact of customer engagement on brand loyalty through customer satisfaction in food parks - Jr., Leoncio T. Lucero (Edelweiss Applied Science and Technology, 2025)
This study investigates the effect of customer engagement on brand loyalty and the mediating role of customer satisfaction among patrons of food parks in Cebu City, Philippines. Utilizing a quantitative research design, data were gathered from 420 randomly selected respondents through a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling (SEM). The model achieved excellent fit indices (CFI = 0.979, TLI = 0.973, RMSEA = 0.066, SRMR = 0.026, χ²/df = 2.849), confirming its validity. Results revealed that engagement significantly influences both satisfaction (β = 0.801, p < 0.001) and brand loyalty (β = 0.628, p < 0.001), while satisfaction also positively affects brand loyalty (β = 0.297, p < 0.001). Moreover, a significant indirect effect of engagement on brand loyalty through satisfaction (β = 0.099, p = 0.005) indicates partial mediation. These findings demonstrate that engaged customers are more likely to be satisfied and develop stronger loyalty toward food park brands. The study highlights the importance of creating engaging and satisfying customer experiences to strengthen brand loyalty. It contributes to understanding the engagement–satisfaction–loyalty framework and offers managerial insights for enhancing customer relationships and loyalty in the competitive food service industry.